Phenetic analysis of natural apricot populations in the Mountainous Dagestan for endocarp (stone) features - D. M. Anatov (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the intraspecies diversity of fruit crop wild relatives is one of the leading trends in botanical and genetic resource research associated with identification and utilization of the phenotypic potential of the population and species, the initial stage in plant breeding and introduction processes, and a prerequisite to solving a number of problems posed by the theory of microevolution, biosystematics and population biology. Currently, large tracts of wild apricot populations (Prunus armeniaca L. = Armeniaca vulgaris Lam.) have been preserved in Central Asia, China and Dagestan. The natural populations of apricot in the Mountainous Dagestan are spread along the valleys of the Avar Koysu, Andi Koysu, Kazikumukh Koysu and Kara Koysu rivers, at altitudes of 350–1500 m ASL, and (sporadically) over the southern slopes – up to 1900 m ASL. They prefer crushed limestone hillsides, where they form the so-called ‘apricot savannah’, rarely assembling into dense massifs. With this in mind, it seems theoretically and practically interesting to evaluate various forms in the diversity of natural apricot populations in the Mountainous Dagestan, with qualitative traits of their endocarp (stone) as a target.Materials and methods. To analyze the diversity of endocarp (stone) forms in natural apricot populations under the conditions of the Mountainous Dagestan, three model cenopopulations (CPs) were selected: in Gunibsky District, along the Kara Koysu (Lower Keger Vlg., 900–1200 m ASL) and Bagdakuli rivers (Salta Vlg., 900–1100 m ASL), and in Levashinsky District, along the Kazikumukh Koysu river (Burtanimakhi Vlg., 1000–1200 m ASL). Stones were collected along the slopes by using transect itineraries. Morphological description of endocarps was made for 328 trees according to 11 qualitative features by standard techniques.Results. A comparative analysis of natural apricot populations showed high variation in the size and shape of the endocarp. Five classes were identified for stone size; of these, the very small (37.8%) and small (37.5%) types had the highest percentage. There were seven types of the endocarp’s shape (rounded, ellipsoid, ovoid, oblong, prolate, teardrop-shaped, and semicordate). Ovoid or rounded shape was observed in an overwhelming majority of apricot trees: their share was 65.3% of the total diversity. Correlation analysis of the endocarp’s features revealed credible positive correlations between the traits (1) ‘keel height’ and ‘rib width’, and (2) ‘lateral rib type’ and ‘rib width’. Creditable negative correlations were found for the trait ‘keel pattern’ with ‘lateral rib type’ and ‘keel height’.